2022
DOI: 10.17014/ijog.9.3.371-381
|View full text |Cite
|
Sign up to set email alerts
|

Calcareous Nannofossil Biostratigraphy of Tonasa Formation at Barru River Traverse, South Sulawesi, Indonesia

Abstract: Barru is one of the areas in South Sulawesi where the stratigraphic sequences of lithology from Mesozoic to recent are well exposed. The Tonasa Formation is quite widespread in this area, and it is interesting to find out its various aspects related to the carbonate rock development. For this reason, the distribution of nannofossils were recorded and the relative age of Tonasa Formation was determined using nannofossil collected by measuring section at Barru River. The calcareous nannofossil assemblages are mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The composition consists of planktonic foraminifera (30%) and mud (70%), rock name is wackestone [14], Figure 3. Studies on the biostratigraphy of nannofossils in the Jeneponto area have been conducted in another place [3].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition consists of planktonic foraminifera (30%) and mud (70%), rock name is wackestone [14], Figure 3. Studies on the biostratigraphy of nannofossils in the Jeneponto area have been conducted in another place [3].…”
Section: Resultsmentioning
confidence: 99%
“…Then these samples were made into thin sections based on differences in texture to determine of rock using a polarizing microscope an objective lens at 50x magnification, and preparation of nannofossils using the smear slides method. The preparation technique is as follows [11]:…”
Section: Methodsmentioning
confidence: 99%
“…Wilson and Bosence (1997) reported that Oligocene strata of the Tonasa Formation in the Jeneponto area were not known. Beside that, the age determination of the Tonasa Formation using nannofossils has already been conducted in Barru area, and yielded a Middle Eocene to Early Miocene age (Farida et al 2022a). From the…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Oligocene to Early Miocene strata are poorly exposed in the Jeneponto area (Wilson and Bosence 1997), although the carbonate succession in this area ranges from the Late Eocene to the Middle Miocene (Sukamto and Supriatna 1982). and from the Middle Eocene to the Early Miocene based on nannofossil assemblages in the Barru area (Farida et al 2022a). A stratigraphic correlation of the Tonasa Formation was obtained between the Pangkajene and Jeneponto areas.…”
Section: Introductionmentioning
confidence: 88%